ANALISIS YURIDIS PEMENUHAN HAK PELAYANAN PUBLIK BAGI PENYANDANG DISABILITAS KABUPATEN JEMBER - Abdul Rozak Aryo Priyambodo; Lutfian Ubaidillah (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Public transportation plays a crucial role in the social and economic structure of cities worldwide by providing access to various services and activities. An efficient transportation system supports mobility in employment, education, healthcare, and recreation, and contributes to inclusive and sustainable urban development. However, individuals with disabilities often face barriers to accessing public transportation, both physical, such as the lack of disability-friendly facilities, and non-physical, such as insufficient staff training and supportive policies. These limitations hinder full participation of individuals with disabilities in society and widen the gap in life opportunities. In Indonesia, issues of inclusion and accessibility for people with disabilities are central to human rights and social justice discourse. Although legislative progress has been made, field practices often remain suboptimal. Regulations such as Article 12 (e) of Regional Regulation No. 7 of 2016 and Law No. 8 of 2016 on Persons with Disabilities provide a legal framework for accessibility, yet implementation on the ground still faces gaps. This study highlights the importance of improving legal protection and enhancing accessibility at public transportation stops in Jember Regency, aiming to identify barriers faced by people with disabilities and provide a basis for advocating for more inclusive policy and infrastructure changes. This research underscores that improving accessibility not only meets practical needs but also ensures recognition and protection of the legal rights of people with disabilities for equal mobility and full participation in society.